Regulatory and pharmacological basis of ayurvedic formulations - Saroya, Amritpal Singh (Boca Raton, Florida : CRC Press, 2016)
The idea of writing a book on such a vast topic was an on-going and vigorous effort. Standard and practical books on the pharmaceutical value of Ayurvedic medicine have been lacking. Standard books incorporating information on standardisation, pre-clinical (animal) and clonocal studies and toxicity data of widely used Ayurvedic formulation have been a missing link.
Introduction to regulatory affairs -- Introduction to ayurvedic pharmacopoeia of India -- Drug Cosmetic Act and ayurvedic drugs -- Ayurvedic drug manufacturing license -- Good manufacturing practices for ayurvedic, siddha, and unani -- Medicines (Schedule-T) -- Ayurvedic drug industry -- Pharmacovigilance of ayurvedic drugs -- Heavy metal content of ayurvedic formulations -- Genotoxicity of ayurvedic formulations -- Aristolochic acid distribution in ayurvedic formulations -- Clinical trials in ayurveda -- National ayush mission -- Ayurvedic pharmacy education -- Patent and IPR issues of ayurvedic formulations -- Ayurvedic pharmacoepidemiology -- Voluntary certification scheme for ayush products -- Ayurvedic databases -- Medicinal Plants Division of Indian Council for Medical Research
Includes bibliographical references and index.
Keywords: MEDICINE, AYURVEDIC -- FORMULAE, RECEIPTS, PRESCRIPTIONS